A demand-side planning approach for the commercial sector of developing countries - Atikol, U (Pergamon-Elsevier Science Ltd, 2004)
A methodology is proposed for collecting end-use demand data for devising demand-side management programs in the commercial sector of developing countries. The characteristics of electricity end-uses in this sector are diverse. The end-use data have been collected in one or two segments of the commercial sector for simplicity and to save time and money. In the case of Northern Cyprus, hotels, a segment of this sector, have a high potential for utility load reduction. A survey was conducted in which questions were asked about the installed capacities of water and space heating, cooling, lighting and refrigeration and their time of use. Typical end-use load curves were obtained for the winter and summer seasons. It is estimated that summer peak could be reduced by approximately 11% if the DSM programs, costing just over half-a-million dollars, are adopted. (C) 2003 Elsevier Ltd. All rights reserved.